Ergonomics car display / Ahmad Zaidi Mukhayor and Mohd Azmir Ahmad - Mukhayor, Ahmad Zaidi; Ahmad, Mohd Azmir (2000)
Self-contained that guide the driver to know what the information they need are gradually becoming important nowadays. The visual information can be displayed on the screen not on dashboard but in a head-up display that projects the information within the driver’s primary field of view, superimposed on the outside road scene. The driver can see the information without the need to look down at the dashboard and without having to adapt visual accommodation substantially. From the research of ergonomics consideration, the ergonomic car display will be design to focus on head up display. In addition, a head-up display provides the driver with better opportunities to correlate the electronically generated information, usually simple graphics, with characteristics in the world outside and so make correct decisions. However, there are a number of factors in producing a well-designed head-up display. These include preventing the loss of all displayed information with a change of drivers head position; designing the graphics (symbol) for maximum comprehensibility and minimum confusion with elements in the outside world; ensuring clear visibility of display and outside scene, both day and night; determining the optimum position and viewing distance of the graphics; establishing the right moment for presenting the information; assessing the acceptance of such systems by their intended users.